數位教材的發展與設計：以高中美術科數位教材為例 The Design and Development of Courseware for High School Art Courses - 何榮桂 (通訊作者); 林燕珍Yen-Jen Lin (Higher Education Foundation, 2011)
近年來，電腦與網際網路上的教學或學習應用已頗為普遍，許多研究指出，有優良品質的數位教材，且善用資訊科技，才能達到真正的教學或學習目標，數位教材的發展與設計必須結合教學、學習、認知和多媒體等理論，有計畫地進行系統化教學設計。教育部近幾年委託高級中學發展各學科之數位教材，將陸續完成17學科的數位教材資源。本文即以高中美術學科數位教材為例，介紹其ADDIE開發流程、數位課程規劃、教材架構、審查作業及製作與應用等，以提供美術科老師認識此豐富的數位教材資源，同時鼓勵傳播使用。Using computers and web resources to enhance teaching and learning has become popularized in recent years. Studies have found that teaching/learning objectives cannot be realized without good digital materials and appropriate use of information technology, whereas the design and development of digital material should incorporate existing theories of teaching, learning, cognition, and multimedia learning into systematic instructional design. Entrusted by Taiwan Ministry of Education, senior high schools began developing digital course materials and tools for each subject and will complete the courseware resources for seventeen subjects in the near future. This study, therefore, taking the art courseware for senior high school for example, introduced the ADDIE training development process, courseware design and development, structure of instructional materials, reviews, applications for effective teaching, etc. in order to serve as a reference guide for art teachers and the general public in teaching and self-learning.